ANALISIS STRATEGI PENGEMBANGAN PERTANIAN MELALUI PENGENDALIAN HAMA TERPADU (PHT) PADI DI KABUPATEN GORONTALO - Widya Kurniati Mohi; Djafar Amin; Herwin Mopangga (Publik : (Jurnal Ilmu Administrasi), 2013)
This study aims to (1) determine how the application of IPM in Gorontalo regency. (2) Determine and analyze the strategy of agricultural development through the application of integrated pest management (IPM) in increasing farm production and welfare in Gorontalo regency. Qualitative research methods were used. Analysis of the data used is a SWOT analysis . SWOT analysis is a form of analysis to maximize strengths and weaknesses and the opportunities and threats meminalisir. The results showed that : (1) Implementation of Integrated Pest Management (IPM) in Rice Gorontalo regency is going well although not maximize, efforts are made to make the technology adoption of Integrated Pest Management (IPM) by farmers in the district of Gorontalo, among others, by socialization IPM integrated through school activities by agricultural extension , training harness and use a variety of agricultural technology (2) In the improvement of agricultural development through the implementation of IPM technology the identified factors are classified into internal and external strengths, weaknesses opportunities and threats to seek and obtain a key success factor the most appropriate strategy in the implementation of rice IPM in Gorontalo regency is SO strategy (incorporating Strengths and Opportunities) that increase the use of quality seeds using cultivation techniques based on the principles of IPM technology is also supported by state funds center is expected to improve its performance in terms of development of agricultural production.